High-resolution, non-contact, cellular level imaging of the cornea of the eye in vivo - Suchand Sandeep, Chandramathi Sukumaran (2023)
Corneal diseases, along with glaucoma and cataract, are the leading causes of blindness worldwide. While corneal surgery offers good success rates, early diagnosis and disease prevention is the preferred choice over expensive and complex surgical procedures. Non-contact, high-resolution imaging modalities for imaging the corneal structures are highly desirable for clinical examinations for early diagnosis of corneal diseases. The currently used clinical standard is the in vivo confocal laser scanning microscopy, which is a contact based method. In this context, an in-house developed, non-contact, Gaussian epi-illumination based imaging system was used to image corneal injury in preclinical animal models in vivo. New Zealand white rabbits and Wistar rats were used as the preclinical models for the investigations. The lateral resolution of the developed system is 1.1 μm. The images obtained with the developed system, as well as the dimensional information of the corneal structures, are in good agreement with the data previously reported using standard methods. The proposed system offers a simple, easy operable, real-time, non-contact imaging modality for the evaluation of corneal structures in high-resolution.